Wearable Devices: Concepts and Applications - Zegarra Rodriguez, Demostenes; Morais de Oliveira, Franck; Nunes, Pedro Henrique; Maria Alves de Morais, Rosalra (INFOCOMP Journal of Computer Science, 2019)
Understanding the human system is essential to describing, monitoring and evaluating human performance based on the signals produced. These signals produced generate information from the human organism, which can be obtained through a technology called, know as wearable sensor. This technology means that by incorporating advanced science and technology into everyday life, it is possible to design and develop wearable devices that can meet the needs of various fields and users. In view of this, this paper presents a review of various applications and concepts of wearable technology, which are currently being discussed by authors in their literatura.